Lanostane-type triterpenes from the fungal endophyte Scleroderma UFSMSc1 (Persoon) Fries. Issue 4 (15th February 2016) - Morandini, Liziane M.B.; Neto, Alexandre T.; Pedroso, Marcelo; Antoniolli, Zaida I.; Burrow, Robert A.; Bortoluzzi, Adailton J.; Mostardeiro, Marco A.; da Silva, Ubiratan F.; Dalcol, Ionara I.; Morel, Ademir F.
Graphical abstract: Sclerodols A and B, two anticandidal lanostane triterpenoids, were isolated from the culture of the Eucalyptus grandis -derived from the fungal endophyte Scleroderma UFSMSc1 (Persoon) Fries, together with the known triterpenoid lanosta-8, 23-dien-3β, 25-diol. Abstract: Two lanostane triterpenoids (sclerodols A and B) were isolated from the culture of the Eucalyptus grandis derived from the endophyte Scleroderma UFSM Sc1(Persoon) Fries together with three known compounds: one related triterpenoid lanosta-8, 23-dien-3β, 25-diol, the disaccharide α, β-trehalose, and the sugar alcohol mannitol. Their structures were elucidated on the basis of 2D NMR, HRME, and single-crystal X-ray diffraction data. The methanol crude extract and the isolated lanostane triterpenoids showed promising anticandidal activities.